Подводная археология. Рец. на кн.: _Бабак Г., Дмитриев А._ Атлантида советского нацмодернизма: Формальный метод в Украине (1920-е – начало 1930-х). М.: Новое литературное обозрение, 2021. 784 с. [Underwater Archaeology. Review of _Atlantida sovetskogo natsmodernizma: Formal’nyi metod v Ukraine (1920-e — nachalo 1930-kh)_, by Galina Babak and Alexander Dmitriev] - Otiakovskii, Valerii (Slavica Revalensia, 2022)
This is a review of a recent book on the formal method’s reception in the Soviet Ukraine. Published in the autumn of 2021, just several months before the beginning of Russia’s war against Ukraine, the book by Galina Babak and Alexander Dmitriev is of particular interest in the light of the inevitable upcoming reconfiguration of Slavic Studies. It both transforms and redefines the well-established ideas concerning the history of Russian (i.e., Moscow-Leningrad) formalism, outlining a previously unknown — and a very original — line of its perception.